Spatiotemporal Distribution Of Parasitic Infections In Al-Najaf Al-Ashraf Governorate And Its Association With Age, Sex, And Seasonal Factors: Distribusi Spasial-Waktu Infeksi Parasit di Provinsi Al-Najaf Al-Ashraf dan Hubungannya dengan Usia, Jenis Kelamin, dan Faktor Musiman - Hawraa Mohammed Al-ali (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Parasitic infections remain a significant public health concern worldwide, particularly in developing regions where sanitation limitations and environmental conditions facilitate transmission. Specific Background: In Iraq, intestinal parasites continue to affect large segments of the population, with infection patterns influenced by demographic and environmental factors. Knowledge Gap: Despite previous epidemiological studies in Iraq, limited research integrates spatial distribution, temporal patterns, and demographic variables simultaneously within Najaf Governorate. Aims: This study investigates the spatiotemporal distribution of parasitic infections in Najaf Governorate and examines their association with age, sex, seasonal variation, and residential location. Results: A total of 422 stool and genitourinary samples collected between July and November 2025 were analyzed, revealing 292 positive cases (69.19%). Five parasites were identified, with Entamoeba histolytica/dispar complex (54.45%) and Giardia lamblia (40.07%) as the dominant species. Infection prevalence was highest among children aged 1–14 years (64.73%), followed by individuals aged 15–44 years (23.63%) and ≥45 years (11.64%). Males showed a higher infection proportion (59.25%) than females (40.75%), while rural residents accounted for 60.27% of positive cases. Seasonal analysis indicated peak infections during July and August. Novelty: The study provides an integrated spatiotemporal and demographic assessment of parasitic infections within Najaf using hospital-based surveillance data. Implications: These findings support targeted public health interventions focusing on sanitation improvement, child health monitoring, and rural disease prevention strategies. Keywords: Parasitic Infections, Epidemiology, Intestinal Parasites, Spatiotemporal Distribution, Najaf Governorate Key Findings Highlights High infection prevalence detected among examined patients in Najaf. Children aged 1–14 years represented the largest proportion of cases. Rural communities recorded higher case distribution than urban populations.